Femmes, artistes et immigrantes : la discrimination multiple à l’égard des écrivaines contemporaines de la diaspora africaine - Zoly Rakotoniera Rakotondravelo (Glad!)
African women writers have struggled to gain a greater place in the literary canon, and immigration has played a key role in this battle. Indeed, much of contemporary African writing emanates from writers living and working outside the countries in which they were born. This essay explores aspects of the literary status of English-speaking African women writers in the diaspora based on the question: How does the intersection of race and gender influence the identity and status of African women writers who have immigrated to Northern countries? Indeed, access to new spaces generates new dynamics that provide them with new and expanded opportunities and the paradoxical realities of otherness. It is a situation that requires more concerted and systematic action. One of the strategies that can serve as a model to fight discrimination is the Caine Prize. The objectives of the Prize as well as the principles on which it is awarded can be seen as actions aimed at eliminating racial and gender inequalities of which the female members of the African Diaspora may be victims.